2020
DOI: 10.1080/21645515.2020.1827609
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of vaccination logistics management among primary health care workers in Nigeria

Abstract: Vaccines are highly thermo-sensitive materials whose potency requires a functional cold chain system which is dependent on the ability of health care workers to effectively manage the system toward eliminating vaccine-preventable diseases.This study assessed knowledge and practice of vaccination logistic management systems among primary health care workers in Osun state Nigeria.It was a descriptive cross-sectional study among 180 randomly selected health care workers who took part in a larger study on the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 4 publications
2
15
6
Order By: Relevance
“…This finding is consistent with a study done in the Ezha district of the Gurage zone [ 46 ], East Gojam zone of Ethiopia [ 27 ], and Western India [ 8 ]. But, this result is higher than a study conducted in Cameroon [ 32 ] and Nigeria [ 26 ]. Thirty-nine percent of the primary health workers knew the proper compartment of the measles vaccine.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…This finding is consistent with a study done in the Ezha district of the Gurage zone [ 46 ], East Gojam zone of Ethiopia [ 27 ], and Western India [ 8 ]. But, this result is higher than a study conducted in Cameroon [ 32 ] and Nigeria [ 26 ]. Thirty-nine percent of the primary health workers knew the proper compartment of the measles vaccine.…”
Section: Discussioncontrasting
confidence: 65%
“…However, It is higher than the figure observed from the study done in the East Gojam zone of Ethiopia, where 38.3% of the respondents had sufficient knowledge about vaccine cold chain management [ 27 ]. It is much lesser than a figure from the studies conducted in Nigeria [ 26 ], and Malaysia [ 48 ] that reported 83.9% and 78.2% of respondents have good knowledge of vaccine cold chain management. This discrepancy might be due to a difference in primary healthcare workers' motivation, qualification, and district health management support.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although LMICs, especially the LDCs, still have a gap in their understanding, attitude, and practice of vaccination cold-chain logistics systems, this does not mean that these countries experience obstacles regarding the transportation, storage, and distribution of routine vaccines, such as the BCG vaccine. A recent study evaluated the knowledge and practice of vaccination logistics management systems among HCWs in Nigeria and the results suggested that 83.9% and 81.1% of HCWs had good knowledge and attitude, respectively, regarding the management systems [ 107 ]. In addition, it has been reported that the stability of the dry powder BCG vaccine did not decrease after storage at 25°C for one year [ 108 ].…”
Section: Opportunities Of Bcg Vaccinementioning
confidence: 99%
“…It is time-consuming and laborious, and the efficiency is not very high. The accuracy of the data is not high enough [7]. (2) Wired monitoring accurately reflects the warehouse storage dynamic data on internal conditions.…”
Section: Introductionmentioning
confidence: 99%